Narrative learning pathways in physical education teacher education - Bonn, Benjamin (Frontiers in Education, 2025)
Different curricular expectations and personal points of view by students intersect in higher education. These perspectives shape the rationale of academic subjects in reference to systemic and individual meanings. Against this backdrop and my previous teaching experiences in teacher education, I re-evaluated my concept for the course of “Personal development and movement education in sport” using a narrative approach to foster individualization and personal relevance. The revised concept provides three different learning paths leading through the courses' subjects. Common ground is the idea of rational decision-making and reflective practice relating research, theory and physical education practice in light of the courses' subjects. Each path establishes its individual nuance, rationale and narration. Key principles are the distinct narrative frameworks for subjects and the opportunity for choice—offering multiple meaning horizons and potentially providing individual learning pathways. Future evaluations will include personal relevance, need satisfaction and learning outcome to further develop this approach based on the students' points of view.